Collaborative teaching-learning between college and industry: A case study of steel practice subj ect matter in the technical faculty ofYogyakarta State University - Suparman Suparman (LPPM UNY, 2008)
Abstract: In vocational secondary school, a collaborative teaching-learning model is known as a dual education system where the students practice in industries. Generally, that system is successful although there are variations among the school. Such collaboration needs relatively high cost and complicated coordination. As an alternative, teaching-learning collaboration between college and industry can be conducted by inviting guest lecturers from the well industry. Thepresent study is aimed at obtaining a model where practice products are marketable and students have co-operative attitudes in team work. Three teaching-learning models are compared. First, the teaching-learning process of thefirst half semester is conducted by a lecturer in college while the rest is conducted by two lecturers in industry. Second, as thefirst, but the teaching-learning process takes place in college only. Third, the teaching-learning process is conducted in college and without collaboration. Students are divided into small groups of 3 or 4 to make marketable products. The products are measured by some college aspects according to industrial standards, whereas co-operative attitudes are measured by Johnson and Johnson definition. The results are subjected to nonparametric statistic analyses. In perspective of the practice product, the first teaching-learning model does not differ significantly from the teaching learning second model (t = 2,2; P 0.05); but differs significantly from the third (t = 4.5; pO.Ol); the second teaching-learning model differs significantly from the third (t = 3.7; pO.Ol). In perspective of the co operative attitudes, the first teaching-learning model does not differ significantly from the second (t=0.81; p0.05). The guest lecturer model is able toproduce marketable products and well co-operative attitudes in a team work.Keywords: collaborative teaching-learning model, well industry, dual education system, guest lecturing, practice products, co-operative attitudes, teamwork